Unraveling the crystal structure of Leptospira kmetyi riboflavin synthase and computational analyses for potential development of new antibacterials - Mohamad Aris, Sayangku Nor Ariati; Raja Abd Rahman, Raja Noor Zaliha; Mohamad Ali, Mohd Shukuri; Jonet, Mohd Anuar; Taiki, Motomura; Muhd Noor, Noor Dina; Mohd Shariff, Fairolniza; Kai-Cheng, Hsu; Thean, Chor Leow (Elsevier BV, 2022)
Over the last decade, an escalating number of reported cases of leptospirosis in Malaysia has resulted in a significant number of deaths. Leptospirosis is caused by Leptospira sp., which is disseminated by soil and water. Due to the absolute dependence of microbes on this biosynthesis pathway coupled with its non-existence in humans, the structural analysis of riboflavin synthase as a potential target for the development of antimicrobial agents is very significant. Riboflavin synthase (E.C 2.5.1.9) is an important enzyme that catalyzes the last stage of riboflavin biosynthesis. Riboflavin synthase from the locally isolated pathogenic bacterium Leptospira kmetyi was cloned and expressed in Escherichia coli. The protein was purified and crystallized for X-ray analysis. The crystal structure of riboflavin synthase from L. kmetyi has been determined at 3.2 Å and belonged to the orthorhombic space group P212121, with an R-factor of 21.8%. The calculated Matthews coefficient (VM) was 2.94 Å3Da−1 with a solvent content of 58.24 %. There are three molecules present in the asymmetric unit. The structure was analyzed with potential inhibitors via molecular docking and molecular dynamics simulation. The complex with compound 1 had the best possible interaction and stability for a 100 ns simulation. The existence of this crystal structure enables its structural properties to be unveiled and facilitates the application of structure-based drug discovery approach. This study sheds light on the development of new potential antibacterial drugs that may be beneficial for the treatment of leptospirosis or other infectious diseases associated with it.